2011
DOI: 10.1111/j.1467-8683.2011.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Did Board Configuration Matter? The Case of US Subprime Lenders

Abstract: Manuscript Type: Empirical Research Question/Issue: The origins of the global financial crisis have been attributed to the combination of a housing price bubble and innovative financial instruments, as well as the lack of restraint by corporate executives and boards to engage in excessive risk-taking. The rise in subprime lending between 1997 and 2005 played a crucial role in inflating the housing price bubble. We take a unique dataset of US financial institutions heavily engaged in subprime lending and ask th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 109 publications
(155 reference statements)
2
61
1
5
Order By: Relevance
“…This negative correlation appears to hold well, irrespective of size, sector and ownership, for established companies as well as for newly incorporated companies. Similarly, recent studies following the 2008 financial crisis also suggest that upper managements with more women engaged less in sub‐prime loans (Muller‐Kahle and Lewellyn, ) and relied less on TARP funds (Bansak, Graham and Zebedee, ).…”
Section: Women In Upper Management and Legal Riskmentioning
confidence: 95%
See 1 more Smart Citation
“…This negative correlation appears to hold well, irrespective of size, sector and ownership, for established companies as well as for newly incorporated companies. Similarly, recent studies following the 2008 financial crisis also suggest that upper managements with more women engaged less in sub‐prime loans (Muller‐Kahle and Lewellyn, ) and relied less on TARP funds (Bansak, Graham and Zebedee, ).…”
Section: Women In Upper Management and Legal Riskmentioning
confidence: 95%
“…Instead, most studies have used variables such as age, functional background, educational background and tenure (Bantel and Jackson, ; Finkelstein and Hambrick, ) in the study of firm risk behaviours such as innovation and international diversification. Furthermore, previous literature examining the risk propensity of women in strategic settings yielded inconsistent results, possibly due to the lack of incorporation of interacting group demographic variables (Johnson and Powell, ; Maxfield et al ., ; Muller‐Kahle and Lewellyn, ). Indeed, Huse () argued that studies should focus on the effects of women on intermediate organizational outcomes and take into account group dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Muller‐Kahle and Lewellyn () examine whether the configurations of board of directors are related to heavy involvement in subprime lending. Using a matched‐pair sample of firms in the financial industry from 1997 to 2005 and conducting panel data logistic regression analysis, they find that subprime lenders had boards that were busier.…”
Section: Board Effectivenessmentioning
confidence: 99%
“…For G8 countries, Yeh, Chung, and Liu () reported that compensation committee independence is helpful for reducing excess managerial risk taking for financial institutions. Muller‐Kahle and Lewellyn () found that the institution of multiple outside directors in financial institutions was associated with more sub‐prime lending for US financial institutions that had established committee systems.…”
Section: Hypothesis Developmentmentioning
confidence: 99%